Determinants of contact tracing apps: an adoption study using UTAUT model - E, Pei Ven; Nor Hazlina Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In the aftermath of the coronavirus (COVID-19) outbreak that impacted human lives globally, a contact tracing app was introduced to control and ease tracking processes via smartphone-based to track positive cases and potential contacts. Major concerns about trust, personal information leakage, and data privacy stored in the system would reserve citizens' willingness to adopt and use the technology. This study focuses on the adoption of contact tracing mobile apps in looking at the key determinants influencing user’s acceptance. An extended Unified Theory of Acceptance and Use of Technology (UTAUT) model was used in this study. A cross-sectional online survey was conducted between September and October2021 and Partially Least Squares (SmartPLS) was used to evaluate about 400 users in Malaysia. The findings revealed that 50.9 % in behavioural intention to adopt a contact tracing app. The highest acceptance rate was among users aged 26 to 35. Effort expectancy was the most important predictor, followed by performance expectancy, perceived risk (of COVID-19), social influence and perceived credibility. Sustainable usage among the users were also being discussed to avoid abundant or inexhaustible use of mobile apps especially relates to health concerns and to prepare for potential new pandemics, such as "Disease X", which were characterised by more infectious and dangerous diseases outbreaks.